Dampak Brand Image dan Customer Experience terhadap Customer Satisfaction (Studi Pada Penonton Bioskop XXI di Surabaya) - Geraldi Yuda Pradipta, Yohanes (Jurnal Ilmu Manajemen, 2020)
The pressures from such high activity will cause tension, fatigue, fatigue, and stress. Currently, the cinema industry has a promising market, shown by people who have high enthusiasm to watch in the cinema. The impact of brand image and consumer experience on cinema consumer satisfaction is an interesting topic to study. This research was intended to investigate and analyze the influence of brand image and customer experience with the satisfaction of cinema viewers in XXI Surabaya. The purposive sampling method was used through the judgmental sampling method for 50 samples. The hypothesis is tested through multiple linear regression analysis. The results of the first tested hypothesis were found that the brand image variable positively and significantly affected the satisfaction of XXI cinema viewers. The results of the second hypothesis test show that the customer experience variable has a positive and significant effect on customer satisfaction watching at the XXI cinema.